(untitled) (Studi di storia medioevale e di diplomatica - Nuova Serie, 2024)
Pomposa’s birth is still shrouded in mystery. The first attestation is known from written sources, in AD 874, and thanks to archaeology, the structures of a small religious building are also known, perhaps dating back to the 6th century, covered by the structures of the medieval monastery. Over the years, various hypotheses have been formulated to explain the flourishing of the extraordinary monastic complex, but the elements are still not very convincing. In this contribution, I will try to demonstrate the territorial context in which the settlement and the weaving of rural properties developed in which it was already established in antiquity and then grew and became the powerful religious complex, located at the intersection of a dense river road network and land which connected the territories controlled by the Archbishop of Ravenna with the properties of the nascent Lombard and Venetian elites. I will try to demonstrate the overlap of the monastery with a vast rural property of ancient tradition and the weight of the cultural influence of Ravenna in the aesthetic choices of the construction of the monastery, from the forms of the church to the selection of the mosaic flooring and the shape of its crypt, to the model of reference for the cloisters, the famous bell tower, and the Palazzo della Ragione.